The occurrence, impacts and dynamics of debris flows in Brazil - Cabral, Victor Carvalho [UNESP] (2023)
Among the landslide types, debris flows represent a greater hazard to society due to their high destruction potential. In Brazil, debris-flow studies are still incipient when compared to other hydrogeomorphic processes and a good understanding of their dynamics is fundamental to supporting hazard and risk assessment studies. In particular, determining the spatialization of events and the extent of the impacts that the phenomenon represents in the country is crucial to supporting targeted and more in-depth studies. In this context, the main objectives of this thesis are to assess the societal impact of debris flows in Brazil and to propose a methodology that aims at reducing the potential damage that future events can cause in susceptible regions. A detailed post-event characterization of a debris-flow event is also conducted, as it is a fundamental step to understanding the phenomenon’s dynamics and can further support the proposal of the hazard assessment methodology. To determine the societal impact of debris flows, a catalogue of events that have caused fatalities and/or economic losses between 1920 and 2021 was created, which supported the debris-flow Mortality Rate (MR) calculation and the application of the so-called F-N Curves (Frequency of events vs. Number of Fatalities). In total, 45 debris-flow events were documented in the considered period, having caused more than 5,773 fatalities and 5.4 billion USD in economic losses. The city of Cubatão (state of São Paulo) shows the highest number of recorded events in the considered period (9), consolidating the status as the most debris-flow prone region in the country. A multi-step hazard assessment is, then, proposed using Cubatão as the test-site, based on the combination of Logistic Regression (LR) analysis, numerical simulation and rainfall back-analysis. The LR results highlight that rainfall is the main influencing factor in debris-flow initiation in the region and indicate the catchments more susceptible to the phenomenon. The simulation results, performed in the catchments indicated by the LR, show that the average runout distance in the region is 470 m, with an average peak flow height of 5 m and a peak velocity of 23 m s-1, according to the calibration based on two past debris-flow events. These results are comparable to the debris-flow event of February 2017 that occurred in the Pedra Branca catchment (Guaratuba, state of Paraná), in which a detailed post-event geomorphological characterization was conducted to estimate the event’s magnitude. The Guaratuba event was of a large-sized stony debris flow, with a total magnitude of 120,195 m3, a peak flow heigh of 7 m and a peak velocity of 26.5 m s-1. Debris-flow events both in Cubatão and Guaratuba are generally triggered by short duration (<48 h), high-intensity (>200 mm) precipitation, with return periods that vary from 3 to 15 years. Five levels of hazard (very low to very high) are, then, proposed in our hazard assessment method, based mainly on the 48-h accumulated rainfall, flow properties (height, velocity) and the spatial analysis of the elements (infrastructures, houses, etc.) at hazard. In Cubatão, industrial and residential areas in the projected debris-flow route generally exhibit the highest overall hazard levels, as many were developed in the depositional area of the phenomenon and near fluvial courses, where associated floods and flash floods may occur. As pointed out by recent studies, an increase in the frequency of extreme precipitation events is projected in the Serra do Mar region and when the general short return period of the debris-flow triggering rainfall is considered (< 20 years), large magnitude (>105 m3) events are likely to occur in the next decade in the portions of the mountain range located in the states of São Paulo and Paraná. This thesis, therefore, is a contribution to better understanding the dynamics of debris flows in Brazil and is a step towards the prevention of future disasters.